2.1.2. A Novel Lead(II) MOF Constructed Through 2-Fold Non-linear FDA as Linker (Communications in Inorganic Synthesis, 2014)
A unique three-dimensional metal-organic framework —— Pb(FDA) (FDA = furan-2,5-dicarboxylic acid) has been hydrothermally synthesized and structurally determined by single-crystal X-ray analysis. The crystal is of tetragonal system, space group I41/a, C6H2O5Pb, Mr = 361.27, a = 13.863(2) Å, b = 13.863(2) Å, c = 13.998(3) Å, V = 2690.0(8) Å3, Z = 16, Dc = 3.568 g/cm3, F(000) = 2560, ?(MuK?) = 25.060 mm-1, Rint = 7.32%, R1 = 2.59% and wR1 = 5.88% for 1543 observed reflections with I > 2?(I). Pb cation is six-coordinated by oxygens of FDA, showing the hemi directed geometry. Pb cations are connected into zigzag chain along b direction in bc planar by FDA, which is furthermore linked to three-dimensional framework with very tiny aperture by bridged carboxyl oxygens of FDA. The elemental analyses, PXRD, FTIR spectra and the thermal stability have been structurally characterized.